DEVELOPMENT REGIONAL ECONOMY IN CONDITION FOR ENSURING THE COMPETITIVENESS OF UZBEKISTAN - R.F., Djumanova; K.F, Egamberdiev (International Journal of Psychosocial Rehabilitation, 2020)
The article substantiates the conduct of a comprehensive regional policy in Uzbekistan. The possibilities of ensuring the competitiveness of the national economy are considered. The factors affecting the country's regional policy are analyzed.